Intermolecular artifacts in probe microscope images of C60 assemblies - Jarvis, Samuel Paul; Rashid, Mohammad Abdur; Sweetman, Adam; Leaf, Jeremy; Taylor, Simon; Moriarty, Philip; Dunn, Janette (American Physical Society, 2015)
Claims that dynamic force microscopy has the capability to resolve intermolecular bonds in real space continue to be vigorously debated. To date, studies have been restricted to planar molecular assemblies with small separations between neighboring molecules. Here we report the observation of intermolecular artifacts over much larger distances in 2D assemblies of C60 molecules, with compelling evidence that in our case the tip apex is terminated by a C60 molecule (rather than the CO termination typically exploited in ultrahigh resolution force microscopy). The complete absence of directional interactions such as hydrogen or halogen bonding, the nonplanar structure of C60, and the fullerene termination of the tip apex in our case highlight that intermolecular artifacts are ubiquitous in dynamic force microscopy.